Reported Subjective Well-Being: A Challenge for Economic Theory and Economic Policy - Alois Stutzer; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2003)
Over the past few years, there has been a steadily increasing interest on the part of economists in happiness research. This paper argues that reported subjective well-being is a satisfactory empirical approximation to individual utility and endeavors to provide an impression of this new, and challenging, development. We study data from the German Socio-Economic Panel to better understand (i) the role of aspirations in the relationship between income and happiness and (ii) the effect of unemployment on people's satisfaction with life. We discuss some of the consequences for economic policy and for economic theory.
Keywords: D60; I31; J60; 330; aspiration level; relative income; subjective well-being; unemployment; utility